Impact of microporous polysaccharide haemostatic agent on patients undergoing mastectomy or axillary dissection on seroma formation and timing of drain removal - Mahmood, Sarah; Brodaric, Alen Maximillian; Srinivasan, Rajkumar; Cohen-Hallaleh, Ruben (International Surgery Journal, 2024)
Background: Seroma formation is a known complication following mastectomy and axillary lymph node dissection (ALND) leading to morbidity and financial implications for patients. ARISTATM AH has been designed to prevent postoperative seromas formation in vitro. Methods: We performed a single institution, single surgeon retrospective study from January 2017 to December 2022 in patients undergoing mastectomy/axillary dissection to evaluate seroma formation rates and timing of drain removal. Results: A total of 72 cases were included in our retrospective review of electronic medical records. Of these, 40 patients underwent ipsilateral mastectomies with sentinel node biopsies, 8 patients underwent bilateral mastectomies, and 18 patients underwent axillary dissections without concurrent mastectomy. Our analysis showed a non-significant decrease in seroma formation when ARISTATM AH was used intra-operatively (10%) compared to standard care (24%), (p=0.14). The ARISTATM AH group had a statistically significantly longer mean drain removal time than the standard care group (12.9 vs 7.6 days, p=0.002). Conclusions: There was a trend towards lower seroma formation and a significantly longer requirement for drain placement after mastectomy in ARISTATM AH group. Further research including randomised controlled multi-centre study evaluating the benefit of topical haemostatic agents in reducing seroma formation in breast surgery is warranted.